The relationship of halal awareness, religiosity, and halal certification on purchasing decisions of halalgood among muslims in Metro Manila - Johaira, Macarambon (2024)
The halal industry is increasing globally due to the increasing population of Muslims. However, in countries with minority Muslim populations, such as the Philippines, the halal industry is still in its early stages. The aim of this study is to investigate the purchase decisions of Muslim consumers in Metro Manila, Philippines, in relation to their halal awareness, religiosity and halal certification. The proposed underpinning theory is the Buyer's Decision Process Theory, which indicates that consumer purchase decisions go through five stages: need recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. Consumer's awareness and religiosity are needs that are continuously researched and evaluated before, during, and after the purchase. A quantitative method was employed with the use of a survey questionnaire. The collected data was analyzed using the International Business Machines (IBM) Statistical Package for Social Science (SPSS) statistical software. The sample data of 384 was determined using the Krejcie & Morgan table. The results indicate that Muslims in Metro Manila halal awareness have strong relationships with purchase decisions on halal food, and religiosity and halal certification have a moderate relationship with purchase decisions on halal food. Findings show that the higher halal awareness, religiosity, and halal certification, the higher the purchase decisions on halal food among Muslims in Metro Manila. This study can contribute to the understanding of Muslim consumers and the Muslim religious sector. It can also assist food manufacturers in creating halal food and the government in crafting policies for the development of halal commerce and the halal ecosystem in the Philippines.